2017
DOI: 10.3389/fmars.2017.00319
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Climate Change on Indigenous Marine Mammal Hunting in Northern and Western Alaska Using Traditional Knowledge

Abstract: Iñupiaq, Yup'ik, and Cup'ik hunters in 14 Alaska Native communities described a rapidly changing marine environment in qualitative traditional knowledge interviews conducted over the course of a decade with 110 individuals. Based on their observations, sea ice conditions are the most notable change, with later freeze-up, thinner and less reliable ice, and earlier and more rapid break-up. Marine mammal populations in northern and western Alaska have been affected by changes in the physical environment, with alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 44 publications
1
46
0
Order By: Relevance
“…Three insights emerged from the study, including: (1) tracking ice conditions along ice trails revealed clear interannual variability in the thickness of the shore-fast ice, (2) documenting trail building and hunting strategies demonstrated how the community responds to variability, and (3) developing CS information resources for the community facilitated interaction with hunters and demonstrated project relevance to environmental challenges facing the community. These insights provided a foundation for the development of a framework to quantify the impacts of loss of sea ice on safety of onice travel and operations across a range of difference icescapes and ice uses (Dammann et al 2018), which remain some of the biggest challenges for Alaska Native marine mammal hunters (Huntington et al 2017). Motivated by the need to forecast safe sea-ice conditions at operational timescales (<10 days), insights from CS-IK sea ice partnerships were included in exploring how IK fits into a forecaster toolbox to support useful sea-ice information products (Deemer et al 2018).…”
Section: Sea Ice and Oceanographymentioning
confidence: 99%
See 2 more Smart Citations
“…Three insights emerged from the study, including: (1) tracking ice conditions along ice trails revealed clear interannual variability in the thickness of the shore-fast ice, (2) documenting trail building and hunting strategies demonstrated how the community responds to variability, and (3) developing CS information resources for the community facilitated interaction with hunters and demonstrated project relevance to environmental challenges facing the community. These insights provided a foundation for the development of a framework to quantify the impacts of loss of sea ice on safety of onice travel and operations across a range of difference icescapes and ice uses (Dammann et al 2018), which remain some of the biggest challenges for Alaska Native marine mammal hunters (Huntington et al 2017). Motivated by the need to forecast safe sea-ice conditions at operational timescales (<10 days), insights from CS-IK sea ice partnerships were included in exploring how IK fits into a forecaster toolbox to support useful sea-ice information products (Deemer et al 2018).…”
Section: Sea Ice and Oceanographymentioning
confidence: 99%
“…Huntington et al 2005, Berkes 2007, Gadamus 2013, ICC-Alaska 2015, Alessa et al 2016. For example, traditional knowledge interviews conducted over the past decade have provided a wealth of information on how marine mammal populations in northern and western Alaska have responded to biophysical changes in the environment (Huntington et al 2017). Although shifts were identified in distribution, abundance, migration, behavior and health, IK indicates that so far marine mammal populations in the region remain healthy and abundant despite changes in the coastal ecosystem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of indigenous knowledge has been emphasized in the context of Arctic and Alaskan climate change adaptation and fish and game management (Arruda & Krutkowski, 2017;Jos & Watson, 2016;Williams & Hardison, 2013;Chapin III, Folke, & Kofinas, 2009). Much of this research relates to using indigenous community knowledge to identify or expand on Western knowledge of environmental change and climate change impacts that contribute to vulnerability (Ignatowski & Rosales, 2013;Huntington, Quakenbush, & Nelson, 2017). Research on how indigenous knowledge has helped Arctic communities adapt to climate change impacts is generally limited to personal subsistence practices, i.e., monitoring subsistence resources, awareness of alternative resources, and knowing how to survive hazardous conditions (Berkes, Colding, & Folke, 2000;Berkes & Jolly, 2001;Pearce, Ford, Willox, & Smit, 2015).…”
Section: Addressing Vulnerability and Building Adaptive Capacity Thromentioning
confidence: 99%
“…Understanding the impact of decreased sea ice extent on polar bear condition, abundance and distribution is essential for their conservation and management. However, at the same time, it is important for management to understand the impact of sea ice loss on subsistence catches (e.g., Huntington et al, 2017) and the human communities that rely on polar bears as a resource. Our primary goal was to gather perspectives from active Inuit polar bear hunters on EG quotas, hunting strategies, and how climate change may be affecting the environment, polar bear distribution, abundance, and biology through time.…”
mentioning
confidence: 99%